PREVALENSI DAN FAKTOR RESIKO INFESTASI Toxocara vitulorum PADA PEDET SAPI POTONG DI KABUPATEN KARANGANYAR - , HANDISTI ELGY SESANTYAMUKTI; , drh. Heru Susetya, MP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Program Swasembada Daging Sapi year of 2014 (PSDS-2014) is one of the efforts to realize food tenacity originated from livestock, based on domestic resources especially beef cattle farm. Factor need to be noticed is health control for some diseases that infect the cattle. One of the diseases that give severe disadvantages is parasitic worm disease. This study aimed to determine the prevalence and risk factors of Toxocara vitulorum infection in calves in District of Karanganyar. The total of 140 samples were taken from four subdistricts in District of Karanganyar. The amount of 12 samples were taken from Jatiyoso subdistrict, 46 samples were taken from Jumantono subdistrict, 20 samples were taken from Matesih subdistrict and 62 samples were taken from Mojogedang subdistrict.The used of feces sample from calves that age less than 6 months were 88 sample, and from the calves that age more than 6 month were 52 sample. All samples were examined using centrifugation method in Laboratorium Balai Besar Veteriner Wates, Yogyakarta. Result data analyzed statistically with chi square test. The result of this study showed that prevalence number of Toxocara vitulorum infection in District of Karanganyar was 7,85%. Several factors which influenced the infection were also analyzed using chi square test and the result showed that stall condition and floor significantly affected (p > 0,05) on Toxocara vitulorum infection in District of Karanganyar.